Fatty acid transport protein 4 is required for incorporation of saturated ultralong-chain fatty acids into epidermal ceramides and monoacylglycerols - Meei-Hua Lin (Nature Portfolio, 2019)
Abstract Fatty acid transport protein 4 (FATP4) is an acyl-CoA synthetase that is required for normal permeability barrier in mammalian skin. FATP4 (SLC27A4) mutations cause ichthyosis prematurity syndrome, a nonlethal disorder. In contrast, Fatp4 −/− mice die neonatally from a defective barrier. Here we used electron microscopy and lipidomics to characterize defects in Fatp4 −/− mice. Mutants showed lamellar body, corneocyte lipid envelope, and cornified envelope abnormalities. Lipidomics identified two lipids previously speculated to be present in mouse epidermis, sphingosine β-hydroxyceramide and monoacylglycerol; mutants displayed decreased proportions of these and the two ceramide classes that carry ultralong-chain, amide-linked fatty acids (FAs) thought to be critical for barrier function, unbound ω-O-acylceramide and bound ω-hydroxyceramide, the latter constituting the major component of the corneocyte lipid envelope. Other abnormalities included elevated amounts of sphingosine α-hydroxyceramide, phytosphingosine non-hydroxyceramide, and 1-O-acylceramide. Acyl chain length alterations in ceramides also suggested roles for FATP4 in esterifying saturated non-hydroxy and β-hydroxy FAs with at least 25 carbons and saturated or unsaturated ω-hydroxy FAs with at least 30 carbons to CoA. Our lipidomic analysis is the most thorough such study of the Fatp4 −/− mouse skin barrier to date, providing information about how FATP4 can contribute to barrier function by regulating fatty acyl moieties in various barrier lipids.